Psychoeducational Application Of Positive Thinking Skills To Reduce Symptoms Of Homesickness In New Students - Ulfatul Muslimah; Muhammad Iqbal Syahsaputra; Siti Suminarti Fasikhah (Research Psychologie, Orientation et Conseil, 2024)
The phenomenon of homesickness often occurs in new students in pesantren. Some of the factors that cause homesickness include feelings of longing for family, dependence on parental assistance, lack of facilities in the dormitory, seniority-related problems, loss of items, illness, a busy schedule of activities, and strict rules.The purpose of this study was to explore the effectiveness of psychoeducation with the application of positive thinking skills in reducing symptoms of homesickness in new students. The method used in this study is psychoeducation type of positive thinking skill with outbound method. The research design applied was one group pre-test posttest, in which the level of homesickness was measured before and after the psychoeducational intervention was given. The results showed that psychoeducation with the application of positive thinking skills had a significant effect on reducing the level of homesickness in new students. This is evidenced by the results of the Wilcoxon test which shows a significance value of 0.000, which means that there is a significant difference between before and after the provision of psychoeducational intervention